Awareness of Garbhopaghatakara Bhavas: A Step Towards Prevention of Teratologic Abnormalities During Pregnancy (International Journal of Ayurveda and Pharma Research, 2025)
Ayurveda is a holistic science which incorporates not only the treatment but also centred for root cause of developmental abnormalities from birth. In present science the presence of teratological abnormalities is a burning issue which inner rates is around 3–5% of live births each year. Garbhopaghatakara Bhavas disrupts the foetus's normal growth and development, includes changes in the mother's food, habits, behaviours, and exposures throughout the perinatal period. Among pregnancy's most devastating outcomes are deformed living foetuses. Anything known to result in foetal abnormalities that a person consumes or is exposed to during pregnancy is referred to as a teratogen. Teratogens include things like chemicals, medications, drugs, some illnesses, and poisonous substances. Additionally, teratogens can raise the chance of stillbirth, premature labour, or miscarriage. Occasionally, the birthing parents have unmanaged health issues. This is an attempt to examine the Garbhopaghatakara Bhavas and teratogenicity during pregnancy of the mother and children. These Garbhopaghatakara bhavas are described under three modes which is dietetics mode of life i.e., Ati Ushana (excessive use of hot), Ati Madhura (excessive use of sweet), Atyalap Bhojana (less quantity of food), Madayapana (using wine daily) etc., physical mode of life i.e., Utakata aasana (squatting or sitting in abnormal position), Vyavaaya (coitus), Vayayaam (improper and excessive exercise), Vegavidharana suppression of natural urges) and mental or psychological mode of life i.e., Bhaya (psychologically constantly fear), Shauka (always distressed or grieved), Karodha (anger), Apriyavlokana sharavanaad (listening to unpleasant words).